2010
DOI: 10.1080/15377900903471989
|View full text |Cite
|
Sign up to set email alerts
|

Effects on Homework Completion and Accuracy of Varied and Constant Reinforcement Within an Interdependent Group Contingency System

Abstract: The present study sought to evaluate the efficacy of an interdependent group contingency program on increasing homework completion and accuracy rates in fourth grade students in an elementary school. In addition, the present study attempted to determine whether randomized reinforcement was more effective than constant reinforcement. Overall, the data suggest that interdependent group contingencies using both constant and varied reinforcement were effective in improving both homework completion and accuracy. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(5 citation statements)
references
References 25 publications
0
4
1
Order By: Relevance
“…The results of the studies by both Kelshaw-Levering et al and Theodore et al suggest that interdependent group contingencies with reinforcement randomization can be successful in decreasing inappropriate classroom behavior. However, Little, Akin-Little, and Newman-Eig (2010), in contrast to most prior research, found constant reinforcement to be more efficacious than varied reinforcement in increasing homework completion.…”
Section: Group Contingenciescontrasting
confidence: 89%
See 1 more Smart Citation
“…The results of the studies by both Kelshaw-Levering et al and Theodore et al suggest that interdependent group contingencies with reinforcement randomization can be successful in decreasing inappropriate classroom behavior. However, Little, Akin-Little, and Newman-Eig (2010), in contrast to most prior research, found constant reinforcement to be more efficacious than varied reinforcement in increasing homework completion.…”
Section: Group Contingenciescontrasting
confidence: 89%
“…Homework was defined as involving a permanent product that was completed outside of regular class time. Both homework completion and accuracy were included in this category (e.g., Aloisio, 2007; Little et al, 2010). Noise level was defined as magnitude of sound, measured in decibels (e.g., Davey, Alexander, Edmonson, Stenhoff, & West, 2001).…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, with dependent contingencies, all members must monitor their behavior, and the target student is randomly selected after the instructional period if reinforcement is earned (e.g., Alric, Bray, Kehle, Chafouleas, & Theodore, 2007). In addition, to maximize the motivation of all students to earn the reinforcer, a Mystery Motivator (MM) can be randomly selected and revealed after the teacher has determined that the criteria for reinforcement were met (e.g., Alric et al, 2007; Little, Akin-Little, & Newman-Eig, 2010; Murphy, Theodore, Aloiso, Alric-Edwards, & Hughes, 2007).…”
mentioning
confidence: 99%
“…Further comparisons found that interdependent group contingencies outperformed individual contingencies and no rewards groups on accuracy and rate of reading (Chapman and Cope 2004). The variations of interdependent group-oriented contingencies, such as randomized reward schedules, have shown promise for spelling ) and math homework accuracy (Little et al 2010). Moreover, the researchers have shown that interdependent group-oriented contingencies may enhance the outcomes when combined with other academic interventions (e.g., Malone and McLaughlin 1997;Pappas et al 2010;Sharp and Skinner 2004).…”
Section: Group-oriented Contingenciesmentioning
confidence: 96%